Konsep 5W+1H dalam Pendidikan (Komparasi Pemikirian Ki Hajar Dewantara dan K.H. A. Wahid Hasyim) - Supriyanti, Iin (Tarbawi: Journal of Islamic Education, 2020)
Education is a conscious effort given by a person through a learning process to form a generation of character, knowledge and religion. Education itself is given by anyone who has more knowledge to humans who have not yet learned. With education it is expected to be able to increase the potential that exists in humans. Speaking of education, there are several figures who play a role in building, optimizing and shaping an education. By looking at the explanation above, the need for an understanding in society about education. In this article, we will discuss aspects of education in 5W + 1H. Namely What is the meaning of education? Who is the real educator? Why is education needed? When is education going on? Where is the education carried out? Abdul Wahid Hasyim was born on June 1, 1914 AD or to coincide with the 5th Wed 'al-awwal 1333 H in Jombang, East Java. He is the son of K.H Hasyim Asy'ari, founder of Nahdlatul Ulama. Ki Hadjar Dewantara was born in Yogyakarta on May 2, 1889. He was the fifth son of Soeryaningrat, the son of Paku Alam III. When he was born, he was given the name Soewardi Soeryaningrat, because he was still of royal descent, he was awarded the title Raden Mas (RM), which later became his full name Raden Mas Soewardi Soeryaningrat. What does education mean? From the two thoughts of the educational figure above, it can be concluded that education is a conscious effort made by someone in printing knowledgeable, character, and religious people. Who are the real educators? According to Ki Hajar Dewantara educating in the real sense is the process of humanizing humanity, namely the appointment of humans to the human level. Educating more liberates people from aspects of inner life (autonomy of thinking and making decisions, dignity, democratic mentality). According to K.H.A. Wahid Hasyim, an educator is not only competent in the field of science, but must master the science of religion. He was guided by the words of the Prophet Muhammad "there is no religion, for people who are not intelligent". Why is education needed? Education takes place at any time, because remembering the human need for education itself is very high. To get an education there is no need for someone to wait for adulthood or the time they have the ability. But education continues as long as someone understands the benefits and functions of education. When does education take place? In understanding the reasons why education is needed, it will be more striking if understood from the aspect of the purpose of education itself. Humans are born with powerlessness, and have different advantages and disadvantages. Humans also have the potential that should be able to develop but humans have weaknesses. For this reason, the purpose of education is the process of human maturity which can bring up potentials in human beings. Where is the education conducted? Ki Hajar Dewantara, who mentioned that the learning environment contained three elements, namely what is known as the education center or tri education center consisting of the realm of the family, the nature of the paguron (school) and the realm of youth (the community). How is the process of implementing education? Based on the theory of learning levels proposed by Ki Hadjar Dewantara, there are four stages of learning. In the implementation of education K.H.A. Wahid Hasyim combines learning models in pesantren with modern learning. Kata Kunci: Konsep 5W+1H, Pendidikan